Comparison of two vasopressor protocols for preventing hypotension post-spinal anesthesia during cesarean section: a randomized controlled trial. Issue 7 (5th April 2021) - Fan, Qian-Qian; Wang, Yong-Hui; Fu, Jing-Wen; Dong, Hai-Long; Yang, Man-Ping; Liu, Duo-Duo; Jiang, Xiao-Fan; Wu, Zhi-Xin; Xiong, Li-Ze; Lu, Zhi-Hong
Abstract: Background: Norepinephrine infusion decreases hypotension after spinal anesthesia during cesarean section. This study aimed to compare the efficacy of norepinephrine infusion and ephedrine bolus against post-spinal hypotension in parturients. Methods: In this double-blinded, randomized controlled clinical trial, parturients scheduled for elective cesarean section were randomly allocated to receive norepinephrine infusion (0.05 μg·kg −1 ·min −1 ) just before spinal anesthesia continuing for 30 min or ephedrine bolus (0.15 mg/kg) just before spinal anesthesia. A rescue bolus (5 μg norepinephrine for the norepinephrine group, and 5 mg ephedrine for the ephedrine group) was administered whenever hypotension occurred. Our primary outcome was the incidence of hypotension within 30 min of spinal anesthesia administration. Secondary outcomes included maternal and neonatal outcomes 30 min after spinal block, and neonatal cerebral oxygenation 10 min after birth. Results: In total, 190 patients were enrolled; of these patients, 177 were included in the final analysis. Fewer patients suffered hypotension in the norepinephrine group than in the ephedrine group (29.5% vs. 44.9%, odds ratio [OR]: 0.51, 95% confidence interval [CI]: 0.28–0.95, P  = 0.034). Moreover, the tachycardia frequency was lower in the norepinephrine group than in the ephedrine group (OR: 0.22, 95% CI: 0.11–0.44, P  < 0.001), and patients suffered less nausea and vomiting (OR: 0.28, 95% CI: 0.11–0.70, P  = 0.004). There was no difference in Apgar scores and umbilical arterial blood gas analysis between the two groups. However, neonatal cerebral regional saturations were significantly higher after birth in the norepinephrine group than in the ephedrine group (mean difference: 2.0%, 95% CI: 0.55%–3.45%, P  = 0.008). Conclusion: In patients undergoing elective cesarean section with spinal anesthesia, norepinephrine infusion compared to ephedrine bolus resulted in less hypotension and tachycardia, and exhibited potential neonatal benefits. Trial Registration: ClinicalTrials.gov, NCT02542748; https://clinicaltrials.gov/ct2/show/record/NCT02542748